Rational design and microwave assisted synthesis of some novel phenyl thiazolyl clubbed s-triazine derivatives as antimalarial antifolate - Jun Moni Kalita; Surajit Kumar Ghosh; Supriya Sahu; Mayurakhi Dutta (SpringerOpen, 2017)
Rational approach to drug design is the process to find new potent molecules on the basis of a known target and available ligands for the target. Compared to the traditional system of drug design and discovery, that involves blind testing of different chemicals in vitro and in vivo in cultured cells and animals, rational approach is totally based on the knowledge of the target and the pathway of action. Recent developments in the field of rational approach to drug design can be credited to the development in the areas of computer science, molecular biology, biophysics, biotechnology and statistics. Designing of new molecules based on the knowledge of receptor and the available ligands is well-known as Structure Based Drug Design (SBDD). The branch of rational approach that uses computer as a tool to design and screen design molecules is called as Computer Aided Drug Design (CADD). In this work computer was used to design and screen the designed molecules virtually. Among the 60 designed molecules 10 were selected on the basis of their binding affinity to the receptor molecule. Synthesis of the selected molecules was done and In-vitro antimalarial activity was evaluated.